A didactic sequence to learn to write. Looking for metalinguistic reflection - Sempere, Joan V. (Linha D'Água, 2023)
This paper aims to present a didactic sequence model resulting from teaching experience. The work as a teacher led us to successive adaptations of Camps and Dolz's proposals. From our regard, when the work is carried out with young students, attention must be paid to the starting linguistic knowledge, but also to the knowledge of the world proper to the age. We have found necessary to relate the sequence to the model of stages of text composition -planning, textualization, revision and correction. Although these procedures are recurring, at this educational level, the chosen model allows to have specific attention to the operations that are performed when writing. We also try to make students participate in their own learning process and attend to the development of metalinguistic and interlinguistic reflection skills, through language contrast.